Sub-clinical Hypothyroidism Fundamentally Associates with Type-II Diabetic Patients: A Clinical Concern to Care Eastern Nepalese People - Jha, Rajneesh (International Journal of Pharmaceutical & Biological Archive, 2017)
The prevalence of thyroid disease, a general health-problem among people, increases as age advances.Hypothyroidism is the most common thyroid disorder among adults and older women. The diabeticpatients have higher prevalence of thyroid disorders compared to normal population. Additionally,hyperthyroidism correlates to worsening of diabetes. Unmanaged pro-diabetics, of both types-I and-II,induce a ‘low T3 state’ characterized by reduced serum total and free T3 levels. The relation betweentype-2 diabetes and thyroid dysfunction has been a less explored domain. It is, therefore, regularscreening for associated thyroid abnormalities in all diabetic patients is essential. This approach willallow practitioner to early treat the correlating thyroid-related problems among diabetics in locality.However, in spite of its vital clinical concern, none of the studies has reported yet about incidences ofthyroid abnormalities among diabetics in eastern Nepal. We, therefore, investigated the status of thyroidabnormalities in type-II diabetic patients in this area. In present study, we observed the significantprevalence of sub-clinical hypothyroidism as 40 %, followed by overt hypothyroidism, sub-clinicalhyperthyroidism and frank hyperthyroidism as 12, 8, and 6 %, respectively. Hence, our data reflects thefact to care for occurrences of thyroid abnormalities among type-II diabetic patients in locality.